Peningkatan Kualitas Sanitasi Lingkungan di Desa Babakanraden - Ade Reza Haryadi; Anisa Pramitasari; Indri Yani (P3M FIA UNKRIS, 2023)
This research was conducted in BabakanRaden Village, Cariu District, Bogor Regency. This is considering several key issues that occur, such as the lack of empowerment regarding how to create and improve a clean and healthy environment by providing knowledge related to Community-Based Total Sanitation (STBM). The results of the KKN activities can be explained and described by the role of community social capital as a form of local population knowledge regarding the importance of environmental sanitation. The process of increasing community knowledge in improving environmental sanitation is carried out through four approaches, namely preparation, socialization, mentoring, and evaluation. Based on the results of these activities, it can be concluded that increasing awareness and character of the community in BabakanRaden Village can be formed and have sustainability through regular socialization and mentoring programs by related parties. In the process of increasing knowledge of good environmental sanitation, mentoring and socialization are in the form of stopping the habit of defecating in the open, getting used to washing hands with soap, planning the construction of toilets, paying attention to the layout of buildings with residences, clean water sources and food sources for local residents, and raising awareness of the importance of maintaining the cleanliness of the local environment and oneself for a healthy life.